2006
DOI: 10.1021/jm0511029
|View full text |Cite
|
Sign up to set email alerts
|

Human PEPT1 Pharmacophore Distinguishes between Dipeptide Transport and Binding

Abstract: The human intestinal oligopeptide transporter (PEPT1) facilitates the absorption of dipeptides, tripeptides, and many peptidomimetic drugs. In this study, a large number of peptides were selected to investigate the structural features required for PEPT1 transport. Binding affinity was determined in a Gly-Sar uptake inhibition assay, whereas functional transport was ranked in a membrane depolarization assay. Although most of the peptides tested could bind to PEPT1, not all were substrates. As expected, single a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 39 publications
11
92
0
Order By: Relevance
“…The translocation was drastically reduced or completely abolished when Trp was positioned in the middle of the tripeptide (Gly-Trp-Val and Pro-Trp-Ile). In a study by Vig et al, it was noted that Trp in the C-terminal position either resulted in a reduced or a complete lack of translocation of dipeptides (22), which is in agreement with our results.…”
Section: Estimation Of Substrate Translocation Via Hpept1supporting
confidence: 94%
See 3 more Smart Citations
“…The translocation was drastically reduced or completely abolished when Trp was positioned in the middle of the tripeptide (Gly-Trp-Val and Pro-Trp-Ile). In a study by Vig et al, it was noted that Trp in the C-terminal position either resulted in a reduced or a complete lack of translocation of dipeptides (22), which is in agreement with our results.…”
Section: Estimation Of Substrate Translocation Via Hpept1supporting
confidence: 94%
“…We found that Trp-Trp-Trp was an inhibitor of hPEPT1 which is in agreement with a previous study (32). Previously, Lys-Arg, Lys-Lys, Lys-Trp, Pro-Arg, Pro-Asp, Pro-Glu, Pro-Gly, Pro-Lys, Pro-Phe, Pro-Ser, ProTyr, Trp-Tyr and Trp-Trp have also been identified as not being substrates for hPEPT1 (22,32). One could speculate that Lys-Arg and Lys-Lys, both having a net positive charge of +2, may have interacted with the assay system, as their method was similar to ours (22).…”
Section: Substrates and Inhibitors Of Hpept1supporting
confidence: 93%
See 2 more Smart Citations
“…These di/tripeptides are removed from the nutrient rich intestinal lumen by a H + /peptide symporter, peptide transporter 1 or PepT1 (1). This transporter is localized to the apical surface of the intestinal villi and has broad substrate specificity.…”
mentioning
confidence: 99%